1999
DOI: 10.1007/bf01279253
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and ultrastructural changes of the floral nectary ofPisum sativum L. during flower development

Abstract: Summary. The floral nectary of Pisum sativum L. is situated on the receptacle at the base of the gynoecium. The gland receives phloem alone which departed the vascular bundles supplying the staminal column. Throughout the nectary, only the companion cells of the phloem exhibited wall ingrowths typical of transfer cells. Modified stomata on the nectary surface served as exits for nectar, but stomatal pores developed well before the commencement of secretion. Furthermore, stomatal pores on the nectary usually cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 39 publications
5
47
0
2
Order By: Relevance
“…Transfer cells were reported for several hydrophilic glands such as salt glands and nectaries (Fahn 1979). Moreover, the considerable plastid-juxtaposed mitochondria population observed in these cells is evidence of a secretion mechanism that requires enhanced energy, which is typical of transfer cells (Razem & Davis 1999).…”
Section: Discussionmentioning
confidence: 98%
“…Transfer cells were reported for several hydrophilic glands such as salt glands and nectaries (Fahn 1979). Moreover, the considerable plastid-juxtaposed mitochondria population observed in these cells is evidence of a secretion mechanism that requires enhanced energy, which is typical of transfer cells (Razem & Davis 1999).…”
Section: Discussionmentioning
confidence: 98%
“…It seems, however, that not all nectary cells in this species are simultaneously involved in secretion since histological sections reveal that, although some epidermal cells may have collapsed, others remain intact and are presumably functional. Although nectary cells can undergo a number of structural changes during the post-secretory stage (Rachmilevitz and Fahn, 1973;Durkee et al, 1981;Sawidis et al, 1989;Nepi et al, 1996;Razem and Davis, 1999), atrophy of protoplasts, as found in nectary cells of H. imbricata, has not been recorded previously.…”
Section: Comparison Of Nectar Secretionmentioning
confidence: 94%
“…Starch is very common in the nectary cells of orchids (Figueiredo and Pais, 1992;Pais and Figueiredo, 1994;Galetto et al, 1997;Stpiczy n nska, 1997) and other plants (Nepi et al, 1996;Graffal et al, 1998;Razem and Davis, 1999;Vesprini et al, 1999) and starch stored within nectary cells can be utilized both as a source of nectar and as a source of energy for highly metabolic processes (Durkee, 1983). Moreover, according to the 'sugar excretion' hypothesis (de la Barrera and Nobel, 2004), high rates of water uptake by flowers may result in the accumulation of considerable amounts of carbohydrates delivered via the phloem.…”
Section: Comparison Of Nectar Secretionmentioning
confidence: 99%
“…Volume densities of thylakoids, starch, plastoglobuli and stroma inside chloroplasts were estimated by measuring the corresponding areas using the pointcounting method (Kutík et al, 1995;Miroslavov et al, 1996;Fagerberg and Bornman, 1997;Razem and Davis, 1999;Vassilyev, 2000;Wheeler and Fagerberg, 2000;Griffin et al, 2001;Gabarayeva and Grigorjeva, 2002;Pechová et al, 2003;Vičánková and Kutík, 2005;Gregoriou et al, 2007;Kubínová and Kutík, 2007;Holá et al, 2008, Mašková et al 2017.…”
Section: Plant Cell Ultrastructure Measurementsmentioning
confidence: 99%